SOCIAL MEDIA BRANDING, DESIGNING A DISPLAY HOUSE, AND COFFEE TABLE BOOK COUNSELING FOR THE IRINA WOMEN'S COMMUNITY - Handriyotopo, Handriyotopo; Sunarmi, Sunarmi; Yuninggar Renaningtyas; Muthia Anas Salma; Reno Abdurahman (International Journal of Social Science, 2024)
Karangnyar is one of the districts that has the potential to become a tourist village. Nglebak Village is one of the many tourist villages that still need branding education assistance. How Ngeblak Village has the potential for every house to utilize land for living barn plants can be recognized through branding strategies by conducting training in utilizing social media as an effective strategy for the IRINA women's community. The first branding strategy is to create a visual identity that is useful for building a different identity, resulting from brand creativity when choosing the most effective logo name. Second, through the design thinking method and branding strategy from Marty Neumeier, he will try to instill an image of a tourist village that is different from the existing one.